Assessing the economic performance of agrivoltaic systems in vineyards – framework development, simulated scenarios and directions for future research - Larissa Strub; Maximilian Wittke; Max Trommsdorff; Max Trommsdorff; Manfred Stoll; Claudia Kammann; Simone Loose (Frontiers in Horticulture)
IntroductionThis paper introduces a framework for assessing the economic performance of agrivoltaic systems (AVS) in vineyards. The study aims to classify factors influencing the profitability of integrating photovoltaic (PV) systems with viticultural practices, emphasizing potential synergistic benefits. Focused on the geographic and climatic conditions of Geisenheim, Germany—home to the first AVS installation in viticulture in Germany—the framework highlights the need to explore economic and operational parameters to assess AVS feasibility.MethodsThe study operationalized its framework by simulating various scenarios based on key variables such as capital expenditures (CAPEX), operational expenditures (OPEX), and revenue streams from grape and energy production. Key factors considered included solar radiation, panel transparency, and regulatory impacts. Scenarios evaluated included: i) Configurations with fully opaque and semi-transparent PV modules. Ii) Adjustments for full mechanization of viticulture practices. Iii) Self-consumption of the produced energy. The framework employed these simulations to evaluate economic outcomes and identify profitability determinants under different conditions.ResultsFindings indicate that under current conditions in Germany, AVS systems are not economically viable for widespread adoption. Key results include: Economic Outcomes: High initial costs (CAPEX) and insufficient revenue from combined grape and energy production lead to negative net present values over a 20-year period across all simulated scenarios. Profitability Determinants: CAPEX and energy prices emerged as critical factors, while viticulture-related costs and revenues had a minor impact on overall profitability. Potential Improvements: Scenarios incorporating multiple positive changes—such as premium wine pricing, higher feed-in tariffs, and increased self-consumption of energy—demonstrated potential for economic feasibility.DiscussionThe study underscores that high CAPEX and low revenues from grape and energy production are the main barriers to AVS profitability. For AVS systems to achieve economic sustainability, substantial reductions in installation costs, increases in energy prices, or technological advances in efficiency are required. Promising configurations combining multiple favorable changes suggest a pathway toward economic feasibility but highlight the need for further development and innovation. The framework provides valuable guidance for future research and investment strategies, emphasizing the importance of: i) Long-term Trials: To evaluate viticultural impacts and synergistic benefits. Ii) Dynamic Models: Incorporating evolving revenue streams, cost structures, and regulatory impacts. iii) Broad Assessments: Exploring the environmental and social benefits of AVS alongside economic performance. Continuous updates to the framework will ensure its relevance, reflecting advancements in PV technology, viticultural practices, and policy environments. This approach will help bridge the gap between renewable energy and sustainable agriculture.